FLIPPED CATECHESIS: UPAYA MEMBANGKITKAN KATEKESE DALAM KELUARGA - Liria Tjahaja; Kanisius Komsiah Dadi (Jurnal Pendidikan dan Kebudayaan Missio, 2022)
Children's faith education is the responsibility of every parent as the primary and first educator. Regarding the catechesis for the preparation of children for the first communion, the idea from the Catechesi Tradendae document (CT, 68) regarding family catechesis is an important matter that needs to be considered. As irreplaceable educators of faith, parents can continue to carry out faith education for their children at every opportunity and throughout their lives. This paper is an idea that emerged from a study that tried to find an alternative model of online catechesis during the Covid-19 pandemic, which was carried out in joint collaboration between parish catechists together with parents and children of prospective first Communion recipients, using the approach flipped catechesis in the family. Qualitative research methods were used to examine field data using observation, interviews, and Focus Group Discussion (FGD) techniques involving several parishes in the Archdiocese of Jakarta (KAJ). One of the parishes in the Tangerang area, namely the Curug parish, was used as a pilot parish to study in-depth the online catechesis practice carried out by parents for children who will receive the first communion in coordination with the parish catechists. In the end, this study recommends an online catechesis model using the google classroom application media which involves the active role of parents of first Communion children. This catechesis model is seen as capable of creating interactive faith communication in family life and becoming an opportunity for the development of family catechesis in the future. In this paper, the catechesis model is called Family Flipped Catechesis.